ANALISIS PENGARUH TEMPERATUR RUANGAN DAN JENIS KEGIATAN TERHADAP CYBERSICKNESS DAN KELELAHAN FISIK - Daniel Willard; Elty Sarvia (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
When carrying out activities in the virtual world, there is a gap between VR device technology and the human body's ability to respond to the virtual world's display, which is called cybersickness. This study uses factors that arise from outside VR, namely physical environmental factors regarding room temperature. In addition, factors that arise from within VR are also used, namely the type of work. This research is experimental with the number of volunteers as many as 9 people. The sampling technique used was purposive sampling and the volunteers had an age range between 20-25 years. The research was conducted using a virtual reality device and a heart rate meter. The variable used is the temperature variable (warm comfortable and optimal comfortable). The software used for this research is Job Simulator by simulating the type of work as a mode variable (type of work), namely office workers and store clerks. The results of the twoway ANOVA test show that the temperature variable, the mode variable, and the interaction between the two variables have no effect on cybersickness and physical fatigue. The results of the paired t-test show that the heart rate before and during the activity is the same. The results of the energy calculation show that each scenario carried out is included in the classification of